2022
DOI: 10.1111/jedm.12316
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Differential Item Functioning Using Posterior Predictive Model Checking: A Comparison of Discrepancy Statistics

Abstract: This study proposes a new Bayesian differential item functioning (DIF) detection method using posterior predictive model checking (PPMC). Item fit measures including infit, outfit, observed score distribution (OSD), and Q1 were considered as discrepancy statistics for the PPMC DIF methods. The performance of the PPMC DIF method was evaluated via a Monte Carlo simulation manipulating sample size, DIF size, DIF type, DIF percentage, and subpopulation trait distribution. Parametric DIF methods, such as Lord's chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Although we used the cutoff of .12 to be practical and consistent with the operational scaling procedure, it is worthwhile to evaluate the effectiveness of various cutoff values for the alternative RMSD statistics. Furthermore, alternative DIF detection methods other than the RMSD statistic can also be investigated in the context of international large-scale assessments (e.g., Joo & Lee, 2022; Joo, Lee, & Stark, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we used the cutoff of .12 to be practical and consistent with the operational scaling procedure, it is worthwhile to evaluate the effectiveness of various cutoff values for the alternative RMSD statistics. Furthermore, alternative DIF detection methods other than the RMSD statistic can also be investigated in the context of international large-scale assessments (e.g., Joo & Lee, 2022; Joo, Lee, & Stark, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we limited the generated data to dichotomous responses and uniform DIF to keep the study manageable and to avoid confounding factors. We investigated uniform DIF because previous studies reported that uniform DIF is more prevalent in operational settings (Joo et al, 2022; Joo & Lee, 2022) and the RMSD is more sensitive to uniform DIF than nonuniform DIF (Buchholz & Hartig, 2019).…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches are generally multidimensional extensions of traditional DIF detection approaches developed for unidimensional tests (e.g., multidimensional SIBTEST (Stout et al, 1987), the IRT likelihood ratio test (IRT-LR; Thissen, et al, 1993;Suh & Cho, 2014), and Multiple Indicators Multiple Causes Model (MIMIC; Lee et al, 2017). However, relatively new multidimensional DIF estimation statistics that provide different estimation algorithms as an alternative to traditional DIF detection methods, have also been developed (e.g., Yuan & Lin, 2006;Bauer et al, 2020;Wang et al, 2020;Joo & Lee, 2022;Lim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The study of differential item functioning (DIF) has a long history in the psychometric literature, dating back to the pioneering work of several psychometricians involved with the Educational Testing Service (ETS; e.g., Donlon, 1981; Dorans & Kulick, 1986), and continues to receive considerable methodological attention (e.g., Joo & Lee, 2022; Wells, 2021). Procedures for detecting DIF are generally well established, and can utilize various strategies based on observed variable and latent variable methodologies (see Millsap, 2011, for an in‐depth presentation).…”
mentioning
confidence: 99%